EVALUATING THE ORAL NARRATIVES OF MINORITY CENTENARIANS: A CASE STUDY IN SOCIAL JUSTICE. (11th November 2018) - Grunder, B; Heinz, M; McCall, G; Bishop, A; Finchum, T
Abstract: The purpose of this study was to qualitatively review the narratives of four minority Oklahoma Centenarians who participated in the Oklahoma 100 Year Life Oral History Project. Two centenarians were African American and two were multiracial (African-American and Native-American). Growing up with fewer opportunities, the impact of living through segregation, and the Tulsa race riots uniquely impacted centenarians in this study. One centenarian vividly remembered attending speaking engagements by Rosa Parks and Martin Luther King Jr. and remains interested and engaged in politics and social justice. Another centenarian remembered traveling to a nearby predominantly African-American town to gain more sense of community, especially during segregation. One centenarian was so deeply affected by her impoverished childhood that she vowed her children would receive an education and always have nice clothing to wear. She remembered being isolated and lonely during her childhood due to the lack of resources her family had. Another centenarian came from a family of educators and taught in a segregated school system, eventually working his way up to principal. Lastly, one centenarian reported that one of the biggest changes he saw in his 100 years of life was a "black president". The distinct experiences noted within oral narratives showcase the types of social justice issues many of these centenarians faced during their life course including poverty, discrimination, and low opportunity. In many cases these disadvantages motivated them to become politically or civically engaged to create change in their communities.